2000
DOI: 10.1002/1521-3803(20001201)44:6<411::aid-food411>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gamma and microwave irradiation of wheat grain on development parameters of some stored grain pests

Abstract: Wheat grain was treated with different doses of gamma irradiation or different times of microwaves. Gamma rays (0.05-10 kGy) caused statistically significant differences in soluble protein contents and kernel hardness. Microwave treatment (15-180 s) resulted in some statistically significant changes in moisture and soluble protein contents. Mortality, intensity of feeding, fertility of adults, progeny number and development time of larvae of the granary weevil (Sitophilus granarius L.) on treated grain were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…That is why research on induced changes in wheat grain caused by c-radiation and microwave heating remains an important and interesting challenge. Therefore, the present work is part of complex investigations aimed to study the influence of c-and microwave radiation on modification of wheat grain biological activities [27], nutritional properties [1], microfloral contamination of grain [28], grain susceptibility to secondary infestation by insect pests [2,3,29], the influence on grain structure [5], technological properties [30,31] as well as on color and odor of wheat grain [4]. The purpose of this study was to investigate the influence of various doses of c-and microwave Grains of the Polish winter wheat variety Begra were subject to c-radiation ( 60 Co) within the dose range of 0.05-10 kGy and microwave treatment from 15 to 180 s, the latter resulting in a bulk grain temperature ranging from 28 to 98 8C.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…That is why research on induced changes in wheat grain caused by c-radiation and microwave heating remains an important and interesting challenge. Therefore, the present work is part of complex investigations aimed to study the influence of c-and microwave radiation on modification of wheat grain biological activities [27], nutritional properties [1], microfloral contamination of grain [28], grain susceptibility to secondary infestation by insect pests [2,3,29], the influence on grain structure [5], technological properties [30,31] as well as on color and odor of wheat grain [4]. The purpose of this study was to investigate the influence of various doses of c-and microwave Grains of the Polish winter wheat variety Begra were subject to c-radiation ( 60 Co) within the dose range of 0.05-10 kGy and microwave treatment from 15 to 180 s, the latter resulting in a bulk grain temperature ranging from 28 to 98 8C.…”
Section: Introductionsupporting
confidence: 55%
“…and Mediterranean flour moth (A. kühniella (Zell.)) reared on the same wheat grain (ground into flour) treated by microwaves became statistically significantly short, when compared to the control grain [29]. The changes observed using SEM were also confirmed by LM which despite of the starch granules disruption showed also the lack of cell content integrity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content of stored water chestnut in various type of storage structure differed significantly with the increase in storage period and radiation treatment. Warchalewski et al (2000) also reported the similar results on wheat grain treated with gamma rays (0.05-10kGy) caused statistically significant differences in protein contents. Figure 8 suggests there was no significant difference among the treatments as regards fat content during the entire storage period of 0(first day first months), 3 and 6 months in glass jar, tin container and LDPE bag.…”
Section: Effect Of Gras Chemical Coating Gamma Radiation and Storagementioning
confidence: 99%
“…Through this approach, the microbiological safety of food can be improved, and its shelf life can be prolonged without substantial alteration [24,25]. Irradiation can also eliminate pests on agricultural commodities; consequently, food losses are minimized and use of chemical fumigants and additives is avoided [26]. The method can reduce the amounts of mycotoxins, such as AFB 1 , ZEN, and OTA [27].…”
Section: Introductionmentioning
confidence: 99%